Application of the servqual method to increase customer satisfaction in renting tronton trucks - Siregar, Syafri Nur Hidayat; Puspasari, Ratih (Journal of Intelligent Decision Support System (IDSS), 2023)
This study aims to apply the ServQual and Importance Performance Analysis methods at PT. Srikandi Transolusindo Intilam to increase customer satisfaction in renting tronton trucks. Feelings that arise as a result of an evaluation of the experience of using a product or service, generally if consumers are not satisfied, there will be an exchange of communication with their environment about dissatisfaction with the producer and will affect the company's brand image which will have an impact as a loss and loss of potential new consumers. The method used for the application of the data is the ServQual and Importance Performance Analysis methods, namely the quality control method. The assessment for this method is that there are two main factors regarding the quality of service, namely the perception that the customer has, and the service received by the customer (perceived service) from the service that the customer expects them to receive (expected service). Based on these results, this method can assess customer satisfaction in renting a tronton truck at PT. Srikandi Transolusindo Intilam.